2017
DOI: 10.1038/s41598-017-02041-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the efficacy of intravenous administration of predatory bacteria in rats

Abstract: The proteobacteria Bdellovibrio bacteriovorus and Micavibrio aeruginosavorus are obligate predators of Gram-negative bacteria, and have been proposed to be used to treat multidrug-resistant bacterial infections. The ability of predatory bacteria to reduce bacterial burden in vivo within the lungs of rats has been demonstrated, but it was unknown if predatory bacteria can attenuate systemic bacterial burden administered intravenously. In this study, we first assessed the safety of intravenous inoculation of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…This experimental result fits with our mathematical model, which predicts the depletion of serum antimicrobial activity in less than 1 hour. This rapid loss of complement activity highlights one of the limitations of using a closed experimental system and should be considered when extrapolating results to some in vivo scenarios such as the circulatory system 38 , but is of relevance to isolated wound sites. It is possible that in a more refreshed system, where serum is replenished by bodily circulation that once prey numbers are reduced below a threshold level by B. bacteriovorus predation the antimicrobial activity of the serum, in combination with leukocytes, may clear the pathogen and the pathogen regrowth we observe in our closed model systems would not occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental result fits with our mathematical model, which predicts the depletion of serum antimicrobial activity in less than 1 hour. This rapid loss of complement activity highlights one of the limitations of using a closed experimental system and should be considered when extrapolating results to some in vivo scenarios such as the circulatory system 38 , but is of relevance to isolated wound sites. It is possible that in a more refreshed system, where serum is replenished by bodily circulation that once prey numbers are reduced below a threshold level by B. bacteriovorus predation the antimicrobial activity of the serum, in combination with leukocytes, may clear the pathogen and the pathogen regrowth we observe in our closed model systems would not occur.…”
Section: Resultsmentioning
confidence: 99%
“…This approach may aid dosing and viable predator-persistence considerations for more systemic studies such as the bloodstream injections of predators recently published by Shatzkes et al . 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In one preliminary study, Kadouri and his colleagues found that injecting Bdellovibrio into veins had no effect on an acute bloodstream Klebsiella infection in rats (2). The chances of predators surviving immune responses, making contact with prey, and consuming them in a systemic infection such as this one are slim, explains microbiologist Nancy Connell of the Johns Hopkins Center for Health Security, who coauthored the study.…”
Section: Inside Animal Infectionsmentioning
confidence: 99%
“…Upon intranasal inoculation in rats, the predator bacteria reduced K. pneumoniae burden in the lungs by 1000-fold (Shatzkes et al, 2016). In contrast, predator bacteria were unable to reduce K. pneumoniae titres in the blood of intravenously infected rats (Shatzkes et al, 2017a). Initial claims for treatment effects against keratitis of the eyes were not confirmed (Boileau et al, 2016), and clinical exploration has thus not yet started.…”
Section: To Tailocinsmentioning
confidence: 99%